2009
DOI: 10.4321/s0004-06142009000500005
|View full text |Cite
|
Sign up to set email alerts
|

Antígeno prostático-específico, citoquinas pro-inflamatorias y patología prostática (Hiperplasia benigna y Cáncer): Relación con la malignidad

Abstract: Summary.-OBJECTIVES: Cancer is a complex process in which cytokines play an important role. Cytokines are low-molecular weight soluble proteins involved in cellular transmission signals and several disorders. Pro-inflammatory cytokines

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…An association has been shown to exist between the cytokines IL-4 and TNF-α and circulating levels of KLK3 [56,57]. KLK3 can also induce proliferation and expression of cytokines from peripheral blood lymphocytes [58,59]. High levels of KLK3 can induce expression of IL-6 and TNF-α and activate an immune response involving both IL-4 and IL-5 in ASD patients [60].…”
Section: Discussionmentioning
confidence: 99%
“…An association has been shown to exist between the cytokines IL-4 and TNF-α and circulating levels of KLK3 [56,57]. KLK3 can also induce proliferation and expression of cytokines from peripheral blood lymphocytes [58,59]. High levels of KLK3 can induce expression of IL-6 and TNF-α and activate an immune response involving both IL-4 and IL-5 in ASD patients [60].…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between the concentrations of SCFAs isolated from patients’ faeces and the tissue expression of pro-inflammatory interleukins (IL-6 and IL-18) was not analysed either. The studies conducted so far, where the expression of IL-6 was confirmed in the immunohistochemical reaction, mainly concerned the differences between BPH and prostate cancer [ 33 ]. These studies have shown that in the case of benign prostatic hyperplasia, high tissue IL-6 expression depends on a high concentration of secreted PSA [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…The studies conducted so far, where the expression of IL-6 was confirmed in the immunohistochemical reaction, mainly concerned the differences between BPH and prostate cancer [ 33 ]. These studies have shown that in the case of benign prostatic hyperplasia, high tissue IL-6 expression depends on a high concentration of secreted PSA [ 33 ]. The studies comparing the factors proving the presence of inflammation analysed, among others, IL-6 concentration [ 34 ].…”
Section: Discussionmentioning
confidence: 99%